Melatonin protects against mercury(II)-induced oxidative tissue damage in rats - ŞENER, GÖKSEL (BLACKWELL MUNKSGAARD, 2003)
Mercury exerts a variety of toxic effects in the body. Lipid peroxidation, DNA damage and depletion of reduced glutathione by Hg(II) suggest an oxidative stress-like mechanism for Hg(II) toxicity. Melatonin, the main secretory product of the pineal gland, was recently found to be a potent free radical scavenger and antioxidant. N-Acetylcysteine, a precursor of reduced glutathione and an antioxidant, is used in the therapy of acute heavy metal poisoning. In this study the protective effects of melatonin in comparison to that of N-acetylcysteine against Hg-induced oxidative damage in the kidney, liver, lung and brain tissues were investigated. Wistar albino rats of either sex (200-250 g) were divided into six groups, each consisting of 8 animals. Rats were intraperitoneally injected with 1) 0.9% NaCl, control (C) group; 2) a single dose of 5 mg/kg mercuric chloride (HgCl2), Hg group; 3) melatonin in a dose of 10 mg/kg, I hr after HgCl2 injection, Hg-melatonin group; 4) melatonin in a dose of 10 mg/kg one day before and 1 hr after HgCl2 injection, melatonin-Hg-melatonin group; 5) N-acetylcysteine in a dose of 150 mg/kg, I hr after HgCl2 injection, Hg-N-acetylcysteine group, and 6) N-acetylcysteine in a dose of 150 mg/kg one day before and I hr after HgCl2 injection, N-acetylcysteine-Hg-N-acetylcysteine group. Animals were killed by decapitation 24 hr after the injection of HgCl2. Tissue samples were taken for determination of malondialdehyde, an end-product of lipid peroxidation; glutathione (GSH), a key antioxidant, and myeloperoxidase activity, an index of neutrophil infiltration. The results revealed that HgCl2 induced oxidative tissue damage, as evidenced by increases in malondialdehyde levels. Myeloperoxidase activity was also increased, and GSH levels were decreased in the liver, kidney and the lungs. All of these effects were reversed by melatonin or N-acetylcysteine treatment. Since melatonin or N-acetylcysteine administration reversed these responses, it seems likely that melatonin or N-acetylcysteine can protect all these tissues against HgCl2-induced oxidative damage.
Keywords: MERCURIC-CHLORIDE; LIPID-PEROXIDATION; INDUCED NEPHROTOXICITY; N-ACETYLCYSTEINE; STRESS; GLUTATHIONE; MICE; KIDNEY; MYELOPEROXIDASE; METHYLMERCURY